Review on Biochemical Composition and Micro-flora of Prawns - Ginson, J.; Bindu, J. (Fishery Technology, 2017)
Prawns are highly demanded seafood commodityboth in domestic and International markets due totheir nutritional value and unique taste. However,its trading is a risky business due to quick perishablenature and the formation of black spots on theexoskeleton. Biochemical composition such as wateractivity, pH and autolytic enzymes of the prawnsignificantly influence the degree of spoilage;moreover, prawns are scavengers and filter feederswhich cause them to accumulate several bacteria intheir body, which also accelerates the spoilageprocess. Hence, basic information regarding thebiochemical composition and micro-flora of prawnare highly relevant to find out suitable preservationtechniques and the production of various valueadded products. This article reviews the availableinformation on the moisture, sarcoplasmic protein,myofibrillar proteins, stroma protein, non-proteinnitrogen (NPN), free amino acid, saturated fattyacids, monounsaturated fatty acids, polyunsaturatedfatty acids (PUFA), mineral content andmicroflora of the prawns.